Pembentukan Karakter Pemuda Gereja Melalui PAK Di Jemaat Germita Baitani Pulutan Kabupaten Talaud - Irene Presilia Ilat; Mariana Lausan; Darmianus Harefa (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to analyze how the Church’s Youth Character Forming Through Christian Religious Education (PAK) in the GERMITA Baitani Pulutan Congregation. This research is a qualitative research, conducted at the GERMITA Baitani Pulutan Congregation. Data were collected through observation, interviews and documentation. Through the results of data analysis, it was found that Church Youth Character Building through PAK in the GERMITA Baitani Pulutan Congregation was still lacking because Pelsus only carried out tasks around worship services, both in the field of worship services in the church or in the field of youth worship services which were carried out once a week. There have been no new innovations such as creative youth spiritual activities such as beach worship, as well as seminars that educate youth to pay more attention to character as church youth. Efforts that must be made by pastors, church councils, elders and parents of youth are character building through PAK such as giving advice and examples to youth and involving them in the field of church ministry and special youth ministry.